Turnip mosaic virus infection cleaves MEDIATOR SUBUNIT16 in plants increasing plant susceptibility to the virus and its aphid vector Myzus persicae - Swayamjit Ray; Tyseen Murad; Gabriella D. Arena; Kanza Arshad; Zebulun Arendsee; Venura Herath; Steven A. Whitham; Clare L. Casteel (BMC Plant Biology)
Abstract Plant viruses both trigger and inhibit host plant defense responses, including defenses that target their insect vectors, such as aphids. Turnip mosaic viru (TuMV) infection and its protein, NIa-Pro (nuclear inclusion protease a), suppress aphid-induced plant defenses, however the mechanisms of this suppression are still largely unknown. In this study, we determined that NIa-Pro’s protease activity is required to increase aphid performance on host plants and that 40 transcripts with predicted NIa-Pro cleavage sequences are regulated in Arabidopsis plants challenged with aphids and/or virus compared to healthy controls. One of the candidates, MEDIATOR 16 (MED16), regulates the transcription of ethylene (ET)/jasmonic acid (JA)-dependent defense responses against necrotrophic pathogens. We show that a nuclear localization signal is removed from MED16 by specific proteolytic cleavage in virus-infected plants and in plants overexpressing NIa-Pro in the presence of aphids. Although some cleavage was occasionally detected in the absence of virus infection, it occurred at a much higher rate in plants that were virus-infected or overexpressing NIa-Pro, especially when aphids were also present. This suggests MED16 functions in the nucleus may be impacted in virus infected plants. Consistent with this, induction of the MED16-dependent transcript of PLANT DEFENSIN 1.2 (PDF1.2), was reduced in virus-infected plants and in plants expressing NIa-Pro compared to controls, but not in plants expressing NIa-Pro C151A that lacks its protease activity. Finally, we show the performance of both the virus and the aphid vector was enhanced on med16 mutant Arabidopsis compared to controls. Overall, this study demonstrates MED16 regulates defense responses against both the virus and the aphid and provides insights into the mechanism by which TuMV suppresses anti-virus and anti-herbivore defenses.